La efectividad del proceso de responsabilidad fiscal verbal de la gerencia departamental del meta de la CGR en la preservación del patrimonio público entre los años 2014-2018 (2022)
Surveillance of the use and proper distribution of public assets is a responsibility not only of the Comptroller General of the Republic but also of the general public; In accordance with the foregoing and in order to achieve this pillar, it is important to have an efficient, effective and transparent Fiscal Process that, in compliance with established principles, guarantees that all activity carried out regarding the execution of resources is carried out in accordance with the norms and procedures indicated by law for this. The effectiveness of any process is put to the test when its scope is evaluated and the results are consistent with the established objectives; For the issue that concerns us, the Fiscal Control Process in Colombia allows to measure the Management carried out by a representative, by any public servant, individual or one who has been in charge of the management, use and distribution of public resources; Said process, through Fiscal Responsibility, seeks compensation for patrimonial damage, as well as generating preventive mechanisms that lead to good management and a reduction in acts of corruption. The regulatory framework that frames the tax process is regulated by the Political Constitution of Colombia, Laws 42 of 1993, Law 610 of 2000 modified by Law 1477 of 2011, the last rule that introduced important changes and on which it is intended to establish its effectiveness. as a compensation mechanism for the State's patrimonial damage